Imaging thermal plasma mass and velocity analyzer. Issue 7 (14th July 2016) - Yau, Andrew W.; Howarth, Andrew
Abstract: We present the design and principle of operation of the imaging ion mass and velocity analyzer on the Enhanced Polar Outflow Probe (e‐POP), which measures low‐energy (1–90 eV/e) ion mass composition (1–40 AMU/e) and velocity distributions using a hemispherical electrostatic analyzer (HEA), a time‐of‐flight (TOF) gate, and a pair of toroidal electrostatic deflectors (TED). The HEA and TOF gate measure the energy‐per‐charge and azimuth of each detected ion and the ion transit time inside the analyzer, respectively, providing the 2‐D velocity distribution of each major ionospheric ion species and resolving the minor ion species under favorable conditions. The TED are in front of the TOF gate and optionally sample ions at different elevation angles up to ±60°, for measurement of 3‐D velocity distribution. We present examples of observation data to illustrate the measurement capability of the analyzer, and show the occurrence of enhanced densities of heavy "minor" O ++, N +, and molecular ions and intermittent, high‐velocity (a few km/s) upward and downward flowing H + ions in localized regions of the quiet time topside high‐latitude ionosphere. Key Points: Imaging plasma analyzer design combines hemispherical electrostatic analyzer, time‐of‐flight gate, and toroidal electrostatic deflector Analyzer measures mass composition and detailed velocity distributions of low‐energy (1–90 eV) ions of 1–40 AMU Observation of large‐velocity flow of minor H + ions and enhanced N + and other heavy "minor ion" densities in quiet time topside ionosphere